South Pacific Agricultural News, September 2007 - Samasoni, Aterina; Umar, Mohammed (IRETA/CTA, 2007)
This issue of the South Pacific Agricultural News (SPAN) deals with a wide variety of issues regarding the South Pacific Agricultural development such as export and market, livestock, Solomon agricultural policy etc.